Plan de acción para la participación de los jóvenes en la justicia indígena de la comunidad Tocagón- 2018 - Zambrano, Lenin A. (2018)
The main objective of the research was to propose a plan of action for the participation of young people in the Indigenous Justice in the community of Tocagon during the year 2018, considering it pertinent from the beginning of progressivity, to include the ideas, criteria and the own vision of the young people in the decision making, in the different cases raised in the council; To do this, a participatory action research was carried out with a mixed approach, so it became necessary to triangulate the information with the responses of the open interview applied to the members of the council and the questionnaire intentionally directed to 100 young people in the community: resulting, that indigenous justice is known by 79% of the members of the community; and that in turn 72% know of its application; likewise, 42% in general participated in it and only 25% of the young people intervened; It is evident that 81% of the community supports the participation of young people in future decisions, considering that 61% are involved. Concluding that young people still do not take the post in the exercise of indigenous justice in the Tocagon Community and that as a constitutional right that assists them, it is necessary to orient a plan of action directed to the place of the referred community that contains the bases and norms already accepted at international and national level by the Ecuadorian state that makes visible the cosmovision of the young Kichwas.